Promoting learner autonomy: Practices of English teachers in Saudi secondary schools - Alhujayri, Israa Ahmed Y. (Edelweiss Applied Science and Technology, 2025)
The promotion of learner autonomy has gained prominence in English language teaching (ELT) as an essential pedagogical goal, particularly within contexts where traditional teacher-centered approaches dominate. This mixed-methods study explores the practices of English language teachers in Saudi secondary schools in promoting learner autonomy. Drawing on quantitative survey data and qualitative open-ended responses from 82 teachers across ten regions, the study reveals a growing awareness among Saudi educators of the importance of student-centered learning. Findings indicate that while many teachers employ autonomy-supportive strategies such as shared decision-making and independent learning activities, systemic constraints—including rigid curricula, exam-oriented instruction, and a lack of professional development—limit their effectiveness. This study contributes to the discourse on educational reform in Saudi Arabia by identifying key areas for teacher training and institutional support to cultivate learner autonomy in ELT contexts.